Mathematical modelling optimisation of centralised sewage treatment plant for electricity generation - Tarmizi, Muhammad Saufi (2022)
Electricity has become one of the most basic requirements of human life. Fossil fuel is the world's leading source of gross electricity production. Alternative fuels have been offered the chance to lessen reliance on fossil fuels while also lowering greenhouse gas emissions. Malaysia's government recently announced a plan to seek green energy alternatives and technology for sustainable development. One of the most promising alternative fuels is biogas, which is produced through anaerobic digestion of sewage sludge in treatment plants. The existing decentralised small-scale sewage treatment plant is currently facing a problem due to a lack of input substrate for a biogas facility of sufficient scale. Furthermore, it necessitates a large plot of land and is difficult to manage due to its scattered placement. As a result, a centralised sewage treatment plant (CSTP) is a viable solution to this issue. The main objective of this research is to develop a model for optimal CSTP planning in generating electricity. The general methods can be divided into 5 stages; data gathering, problem formulation and superstructure construction, model development, general algebraic modeling system software coding and result analysis. The first phase includes creating a single-period model with the primary purpose of lowering capital costs. The second phase is the development of a multi-objective model that maximises economic performance while reducing environmental effect. The third phase is to develop a multi-period model for planning till 2035. Biogas from anaerobic digestion is estimated to be capable of producing 2,140 GWh of power in Peninsular Malaysia in 2018. In terms of economics, electricity generation, and sewage management, the model produced significant improvements over current practise. According to the first model, the total cost of building CSTP is RM175,014,755, which will serve around 400,000 population equivalent and produce 5,767 MWh of electricity per year. The second model calculated the total cost as RM250,880,000 with a multi-objective factor, ?, of 0.56 and a capacity of 7,699 MWh electricity per year. The final model concluded that co-digestion is the best solution for increasing biogas production. Two CSTPs were proposed to meet electricity demand and available sewage at a total cost of RM1,217,416,734 and to generate 56,943 MWh of electricity per year. This research can be used as a preliminary study for CSTP by policymakers and government bodies, allowing them to draw conclusions about the technical and environmental aspects of the transition from existing decentralised to centralised systems. This model can be further developed into usable software that assists relevant authorities in making decisions.